Bioactive polycyclic polyprenylated acylphloroglucinols from Hypericum perforatum. Issue 43 (18th October 2018) - Guo, Yi; Zhang, Na; Sun, Weiguang; Duan, Xueyan; Zhang, Qing; Zhou, Qun; Chen, Chunmei; Zhu, Hucheng; Luo, Zengwei; Liu, Junjun; Li, Xiao-Nian; Xue, Yongbo; et al.
Abstract : Fifteen new polycyclic polyprenylated acylphloroglucinols with dual-targeted inhibitory activities for Alzheimer's disease, were isolated from Hypericum perforatum . Abstract : Fifteen new polycyclic polyprenylated acylphloroglucinols (PPAPs), hyperforatones A–O (1–15 ), along with 3 structurally related analogues (16–18 ), were isolated from the stems and leaves of Hypericum perforatum . Their structures and absolute configurations were established by a combination of NMR spectroscopic analyses, experimental and calculated electronic circular dichroism (ECD), modified Mosher's methods, Rh2 (OCOCF3 )4 - and [Mo2 (OAc)4 ]-induced ECD, X-ray crystallography, and the assistance of quantum chemical predictions (QCP) of 13 C NMR chemical shifts. Compound5 was found to be the first PPAP decorated by a rare 2, 2, 4, 4, 5-(pentamethyltetrahydrofuran-3-yl)methanol moiety and an oxepane ring. Furthermore, the isolates were screened for their acetylcholinesterase (AChE) and β-site amyloid precursor protein cleaving enzyme 1 (BACE1) inhibitory activities. Compounds5, 10, 11, and15 showed desirable AChE inhibitory activities (IC50 6.9–9.2 μM) and simultaneously inhibited BACE1 (at a concentration of 5 μM) with inhibition rates of 50.3%, 34.3%, 47.2%, and 34.6%, respectively. Interestingly, compound5 showed the most balanced inhibitory activities against both AChE and BACE1 of all the tested compounds, which means that5 could serve as the first valuable dual-targeted PPAP for the treatment of Alzheimer's disease. Preliminary molecular docking studies of5 with BACE1 and AChE were also performed.